Remembering Droughts and Abundance: Ecological Memory in the Semi-arid Region of Northeast Brazil - Pereira, Renan (Anthropologica)

(untitled) (University of Victoria, 2024)
In Floresta, a municipality in the semi-arid region of Northeast Brazil, the past is considered a time of greater regularity of the climate, natural wealth of the Caatinga biome, and solidarity among the residents of the city’s rural area. Memories of certain historical events can refer to an ‘ancient time’ in which ‘abundance,’ despite the calamities generated by droughts throughout the occupation of this territory, is considered one of its main socio-ecological attributes. In the context of the violent climatic transformations of contemporaneity, analyzing the actions of the memory of old inhabitants of the Brazilian semi-arid region will be a way of first, ethnographically questioning the history of droughts to which the entire ecology of this region has been reduced by historiography and national literature; second, inquiring the human centrality of modern memory—still today a defining theoretical paradigm of social and cultural studies of memory in anthropology. To this end, memories of droughts and abundance will be articulated with the concept of “duration” (la durée) of French philosopher Henri Bergson to think of memory and the duration of time as a way of ecologically living the past, the present, and the future.